Applied biochemistry and biotechnology : proceedings of twenty-ninth symposium on biotechnology for fuels and chemicals : held April 29-May 2, 2007, in Denver, Colorado - Proceedings of the Symposium on Biotechnology for Fuels and Chemicals (29th. : 2007 : Denver, Colorado); Adney, William S.; McMillan, James D. (London : Humana Press, 2008)
PSZJBL